2016
DOI: 10.5812/traumamon.20013
|View full text |Cite
|
Sign up to set email alerts
|

Fireworks-Related Injuries in Iran: A Survey Following the 2014 New Year’s Festival in Tabriz

Abstract: BackgroundIranian people celebrate the last Wednesday eve of the year as Chaharshanbe Suri and use explosives and firecrackers as part of this festival.ObjectivesThis study concerned fireworks injuries related to the Chaharshanbe Suri festival in Tabriz, a provincial capital in East Azerbaijan, Iran, to evaluate the epidemiology and provide data to prevent and manage these accidents.Patients and MethodsThis study was comprised of patients who were treated at the emergency department of Tabriz Sina hospital wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A number of articles reported burn injury patterns from specific mechanisms including the following: portable heaters, 62 camphor burns, 63,64 combat burns, 65 hot press, 66 campfire burns, 67 friction burns, 68 Freon (contact frostbite), 69 e-cigarettes, [70][71][72][73][74][75] firework injuries, [76][77][78][79][80][81][82][83][84][85][86][87] liquified petroleum gas, 88 hot milk/oil, 89 jewelry ring associated, 90 hot water bottles, 91 and heat lamp burns on replanted digits and free flaps. 92 One case of a patient with Raynaud's phenomenon and hand burns had good outcomes with the use of sildenafil during the burn and split skin graft (SSG) healing.…”
Section: Specific Burn Etiologies or Associationsmentioning
confidence: 99%
“…A number of articles reported burn injury patterns from specific mechanisms including the following: portable heaters, 62 camphor burns, 63,64 combat burns, 65 hot press, 66 campfire burns, 67 friction burns, 68 Freon (contact frostbite), 69 e-cigarettes, [70][71][72][73][74][75] firework injuries, [76][77][78][79][80][81][82][83][84][85][86][87] liquified petroleum gas, 88 hot milk/oil, 89 jewelry ring associated, 90 hot water bottles, 91 and heat lamp burns on replanted digits and free flaps. 92 One case of a patient with Raynaud's phenomenon and hand burns had good outcomes with the use of sildenafil during the burn and split skin graft (SSG) healing.…”
Section: Specific Burn Etiologies or Associationsmentioning
confidence: 99%
“…A final subset of studies focused on types of blast-related burn exposures that are largely unrelated to military settings but that nevertheless might have lessons that are relevant in the military context. Related studies have chronicled the epidemiology of burn injuries from pressurized aerosol cans (Langbart and Vandervord, 2011), electrical equipment (Mashreky et al, 2011;Olaitan, Oseni, and Olakulehin, 2011), and fireworks in settings ranging from the United States (Sandvall et al, 2017;Stahlman and Taubman, 2018) to Iran (Shams Vahdati, Hemmate Gadim, and Mazouchian, 2016;Tavakoli et al, 2011;Vaghardoost et al, 2013). Among these, Stahlman and Taubman, 2018, found that 302 firework-related injuries were reported from 2008 to 2017 and that incidence of injury was higher among those who were U.S. Army members, those in enlisted rank, and those in combat-specific occupations.…”
Section: Prevalence Of Alternative Burn-injury Profiles In Military A...mentioning
confidence: 99%